2015
DOI: 10.1108/ajim-04-2015-0061
|View full text |Cite
|
Sign up to set email alerts
|

Competitive intelligence theoretical framework and practices

Abstract: Purpose – The purpose of this paper is to summarise previous studies to develop a theoretical framework useful to describe and classify competitive intelligence (CI) practices. It is applied to study CI practices developed by Spanish universities, comparing usual practices with those developed during the process of adaptation of degrees to the European Higher Education Area (EHEA), with strong challenges. Design/methodology/approach – Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…[…] collection, transmission, analysis and dissemination of publicly available, ethically and legally obtained relevant information as a means of producing actionable knowledge for the improvement of corporate decision making and action (Garcia-Alsina et al , 2015).…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
“…[…] collection, transmission, analysis and dissemination of publicly available, ethically and legally obtained relevant information as a means of producing actionable knowledge for the improvement of corporate decision making and action (Garcia-Alsina et al , 2015).…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
“…Managers sometimes fail to learn the true meaning of ‘competitive intelligence’ and do not link this discipline to strategic planning (Köseoglu et al, 2016), as was confirmed in research by Lucas et al (2016) for the Brazilian scientific production. Reality has shown that the term itself is not well known by firms in general (García-Alsina et al, 2016; Postigo, 2001). In the case of Spain, among other aspects, this is because of the absence until only a few years ago of the denomination of intelligence as a discipline in the scientific and professional corpus.…”
Section: Methodsmentioning
confidence: 99%
“…All 37 All sizes [Barnea, 2016] Israel All 39 Large [Garcia-Alsina et al, 2016] Spain Education 14 Large [Munoz-Canavate, Alves-Albero, 2017] Spain All 47 Large [Drieman, 2018] Global All 408 All sizes Europe All 156 All sizesgenerally SCIP [Crayon, 2020] Primarily North America All 1000 All sizes tributors, consumers, government, processes, products, and competitors. Being a part of a business ecosystem provides mechanisms to leverage technology, achieve excellence in research and business competence, and compete effectively against other companies.…”
Section: South Africamentioning
confidence: 99%